Model Predictive Control For A Three Phase PMSM Machine - Plugaru, Tudor-Stefan; Nascu, Ioan; Nascu, Ioana (International Conference on System Theory, Control and Computing, 2025)
This paper presents a model based predictive control algorithm for a three phase PMSM machine and a comparison between this control method and a classic PI controller. To increase the robustness an observer is introduced, then a state transformation is performed for a more easily handle of the algorithm. Both cases are discussed, namely without and with constrains, in the end introducing constraints on the control signal increment over all control window. Terms like control window, prediction window and tuning parameter will be introduced to fine tune the control method.